Penerapan Sanksi Adat Kawin Sesuku di Nagari Ranah Koto Tinggi, Kabupaten Pasaman Barat - Mardhatillah, Ummi; S, Nurman; Moeis, Isnarmi; Dewi, Susi Fitria (Journal of Civic Education, 2024)
Endogamy, or marriage within the same tribe, is prohibited under Minangkabau customary law, which imposes specific sanctions for such violations. This study aims to explore the application of customary law concerning endogamy in Nagari Ranah Koto Tinggi, as well as the challenges encountered in its enforcement. A qualitative research approach was employed, utilizing descriptive methods. Data collection was conducted through observation, interviews, and documentation. The analysis process involved data reduction, presentation, and conclusion drawing. The findings indicate that the application of customary law in Nagari Ranah Koto Tinggi is selectively enforced, targeting only marriages within the tribe involving members of the urang nagari or datuk's descendants. However, the enforcement of these sanctions faces several challenges, particularly in the weak implementation of punishments. To address these issues, strategic interventions involving community engagement and local government initiatives are necessary, including education and socialization efforts to emphasize the importance of upholding traditional values and understanding the implications of endogamy.